MANAGEMENT OF PATIENTS ON ANTICOAGULANT THERAPY UNDERGOING DENTAL SURGICAL PROCEDURES. Review Article. - Atanaska Dinkova; Donka G. Kirova; Delyan Delev (Peytchinski Publishing, 2013)
Dental treatment performed in patients receiving oral anticoagulant drug therapy is becoming increasingly common in dental offices.The aim of oral anticoagulant therapy is to reduce blood coagulability to an optimal therapeutic range within which the patient is provided some degree of protection from thromboembolic events. This is achieved at the cost of a minor risk of haemorrhage. Frequently raised questions concern the safety and efficacy of the various anticoagulation regimens and their accompanying thromboembolic and bleeding risks relative to invasive dental procedures.The aim of this literature review is to evaluate the available evidence on the impact of anticoagulant medications on dental treatment and highlight certain patient management issues closely interrelated to various aspects of dental treatment. For that purpose literature search in the electronic database of Medscape, Pubmed-Medline, Science Direct, and EBSCO host, in the data base of Medical University Plovdiv and specialised published books in general medicine and dentistry was made.A total of 33 publications between 1995 and 2013 were identified: 12 review articles, 11 randomized controlled and non-randomised studies, 6 guidelines and practical guides, 1 meta-analysis and 3 specialised books.